Systematic Analysis of Indicators for Socio-Economic Security - D. N. Shvaiba (Наука и техника)
Conducting a systematic analysis of indicators for socio-economic security it is necessary to point out that fundamental groups of characteristics pertaining to socio-economic security include the following indicators: social standard and quality of living, degree of socio-economic system security, level of national financial independence, situation with management system and provision of socio-economic security. All the mentioned and some other indicators have something in common while ensuring socio-economic security and, for this reason, it is important to keep their balance and coherence. Evaluation of socio-economic security for a macro-system can be implemented among other tasks while using matrix method. According to this method it is possible to evaluate a possibility of threat appearance due to changes in a specific indicator, level of impact on national security, duration and time rate of changes in unwanted manifestations. The matrix makes it possible to classify those dangers when there is a possibility of an unsafe situation occurrence to such extent that it is required to undertake urgent measures to improve the situation and take special actions. The proposed method demonstrates visible results and it is considered as a statistical method of analysis. The given method presents rather good results while making smooth changes in evolutionary characteristics of the system. Monitoring horizon of these models is 1–2 years. In this context it is necessary to take into account that the proposed method is hardly suitable in the case when there are prompt changes in characteristics from one group of indicators to the other one. This is due to the fact that statistics of past periods has been applied and it characterized the given system which was under completely different circumstances at that moment. If this is the case then there is a discrepancy in creation of methods at all levels of socio-economic systems and these methods adequately take into account dynamics of changes in the system.